The cost of a healthy and sustainable diet - who can afford it? - Laurel Barosh; Sharon Friel; Katrin Engelhardt; Lilian Chan (Elsevier, 2014)
Abstract Objective: Climate change is affecting the ability of food systems to provide sufficient nutritious and affordable foods at all times. Healthy and sustainable (H&S) food choices are important contributions to health and climate change policy efforts. This paper presents empirical data on the affordability of a food basket that incorporates principles of health and sustainability across different food sub‐systems, socioeconomic neighbourhoods and household income levels in Greater Western Sydney, Australia. Methods: A basket survey was used to investigate the cost of both a typical basket of food and a hypothetical H&S basket. The price of foods in the two baskets was recorded in five neighbourhoods, and the affordability of the baskets was determined across household income quintiles. Results: The cost of the H&S basket was more than the typical basket in all five socioeconomic neighbourhoods, with most disadvantaged neighbourhood spending proportionately more (30%) to buy the H&S basket. Within household income levels, the greatest inequity was found in the middle income neighbourhood, showing that households in the lowest income quintile would have to spend up to 48% of their weekly income to buy the H&S basket, while households in the highest income quintile would have to spend significantly less of their weekly income (9%). Conclusion: The most disadvantaged groups in the region, both at the neighbourhood and household level, experience the greatest inequality in affordability of the H&S diet. Implications: The results highlight the current inequity in food choice in the region and the underlying social issues of cost and affordability of H&S foods.